Validation of model for wheat yield prediction potential using active optical sensor - Grohs, Daniel Santos (2011)
The objective of this work was to validate a model based on the normalized difference vegetation index (NDVI) for the prediction of spatial variability of accumulated biomass in shoots and wheat grain yield. Georeferenced readings of NDVI and biomass, at the end of tillering, and of grain yield were carried out. The proposed method allowed relating classes of spatial variability of NDVI and biomass, with 81% of correspondence between them. However, the relation between spatial variability of yield and NDVI was lower, with 48% of correspondence.